2017
DOI: 10.1016/j.schres.2016.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem structural studies of the thalamus in schizophrenia

Abstract: In this review, we seek to answer the following question: Do findings in the current literature support the idea that thalamo-cortical dysfunction in schizophrenia is due to structural abnormalities in the thalamus? We base our review on the existing literature of design-unbiased stereological studies of the postmortem thalamus from subjects with schizophrenia. Thus, all reported results are based upon the use of unbiased principles of sampling to determine volume and/or total cell numbers of thalamus or its c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 44 publications
(93 reference statements)
6
49
0
1
Order By: Relevance
“…; Kemether et al. ; for review Dorph‐Petersen & Lewis, ). Postmortem quantification of neurones in PM reveals decreased density in SCZ patients, which in the absence of signs of neurodegeneration and scarring has been attributed to disrupted neurogenesis (Byne et al.…”
Section: Association With Neurodevelopmental Disordersmentioning
confidence: 99%
“…; Kemether et al. ; for review Dorph‐Petersen & Lewis, ). Postmortem quantification of neurones in PM reveals decreased density in SCZ patients, which in the absence of signs of neurodegeneration and scarring has been attributed to disrupted neurogenesis (Byne et al.…”
Section: Association With Neurodevelopmental Disordersmentioning
confidence: 99%
“…to note that the thalamus, through its higher order nuclei, is a major relay center with connections to the cerebral cortex, striatum, and cerebellum, which modulate a number of cognitive domains. 37 The thalamus is also one of the brain regions that is most affected in SZ and BD as evidenced by alterations in neuronal number, volume, neurochemistry, functional activation, and structural connectivity. [37][38][39] Thus, axonal damage caused by aberrations in the microvasculature or in inflammatory and oxidative stress pathways may result in RTSD that can be examined through the eye, but no studies to date have tested this hypothesis in SZ or BD.…”
Section: Rnfl Findingsmentioning
confidence: 99%
“…33 It is possible that thinning of the GCL-IPL may be related to neuronal loss and/or synaptic pruning, which are prominent pathophysiologic hypotheses in SZ, though further systematic studies are needed. 37,45…”
Section: Gcl Gcl-ipl and Gcc Findingsmentioning
confidence: 99%
“…Postmortem studies of these nuclei have reported smaller volume and lower number of neurons and/or oligodendrocytes in SCHZ patients as compared with healthy individuals (Byne et al, 2009; Dorph‐Petersen & Lewis, 2017). However, there is a large discrepancy in findings across postmortem studies (Dorph‐Petersen & Lewis, 2017).…”
Section: Introductionmentioning
confidence: 99%